T1 mapping of the remote non-infarct myocardium for predicting adverse left ventricular remodeling following STEMI. (25th November 2020) - Lorenzatti, D; Vega, J; Perea, R.J; Prat, S; Doltra, A; De Caralt, T; Lopez, T; De Diego, O; Ortiz Perez, J.T
Abstract: Background: Adverse Left Ventricular (LV) remodeling (ALVR) following ST-segment Elevation Myocardial Infarction (STEMI) is the result of numerous mechanical, neurohormonal, micro and macrovascular factors, and remains a major clinical problem. Cardiac Magnetic Resonance (CMR) is a multimodality technique that provides comprehensive functional and tissue characterization of infarcted and non-infarcted myocardium. Whether changes in the extracellular matrix in the remote myocardium in patients following a STEMI are associated with adverse LV remodeling has been a topic of debate. Aim: We explored the additive value of native T1 variation (ΔnT1) and derived-extracellular volume (ECV) fraction in the remote non-infarcted myocardium as predictors of adverse LV remodeling following STEMI. Methods: A total of 99 subjects (83% male) with their first mechanically reperfused STEMI underwent CMR within 2 weeks and at 6 months, including T1 mapping prior and 15 to 20 minutes following a bolus of gadolinium (0.2 mmol/kg), with a MOLLI sequence. ECV and nT1 values were computed by averaging co-registered ROIs in three distinct segments in the remote non-infarcted myocardium. Results: Baseline nT1 but not ECV correlated with infarct size (r=0.349, P<0.001 and r=0.162, P=0.096 respectively). In addition, ΔnT1 but not ΔECV correlated with an increase in LV end-diastolic volume index (LVEDVi) (r=0.268, P<0.01 and r=0.113, P=0.285). ALVR, defined as Δ>20% inLVEDVi, occurred in 21 cases, despite optimal medical therapy. Subjects with ALVR showed greater ΔnT1 (13.2±44.1 vs −5.2±30.2 ms, P<0.05) but no significant differences in ΔECV (1.27±2.77 vs 0.72±2.45%, P=0.401). Also, subjects with ALVR were more likely hypertensive (67 vs 33%, P<0.05), had more segments with microvascular obstruction (2.1±2.2 vs 0.8±1.7, P<0.01) and lower baseline EF (39.8±8.8 vs 44.6±9.6%, P<0.05). Infarct size was not significantly larger in ALVR subjects (20.7±13.4 vs 17.5±13.0% LV mass, P=0.322). A multivariate analysis including all these factors, showed the extent of microvascular obstruction (ExpoB: 1.35 [1.05–1.73], P=0.019) and remote ΔnT1 (ExpoB: 1.02 [1.00–1.03], P=0.026) to be the independent predictors of ALVR. Conclusions: The nT1 variation in remote non-infarcted myocardium and the extent of microvascular obstruction are superior to ECV changes and infarct size in predicting ALVR following STEMI. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Fundaciό La Maratό TV3 2015 30 31 32. Fondos FEDER